Influence of TikTok, Influencers, and Prices on Global Consumer Decisions - Muhammad Haris Rahmadana; Lilik Indayani (Indonesian Journal of Law and Economics Review, 2024)
The emergence of social media platforms has revolutionized marketing strategies, offering new avenues for influencing consumer behavior. This study investigates the impact of TikTok social media, influencers, and prices on purchase decisions, focusing on Mie Gacoan noodles in East Java, Indonesia. With a lack of known population size, non-probability purposive sampling was employed, gathering data from 100 respondents via online questionnaires. Utilizing quantitative techniques and hypothesis testing, SPSS software facilitated data analysis. Findings reveal a significant positive effect of TikTok, influencers, and prices on purchase decisions. This research addresses a gap in understanding the influence of emerging digital marketing channels on consumer choices, providing valuable insights for marketers and policymakers. Highlight: TikTok influence: Analyze purchase decisions. Influencers' effect: Examine consumer behavior. Pricing impact: Assess purchase choices. Keywoard: Social Media, Influencers, Prices, Purchase Decisions, Consumer Behavior